“ADVANTAGES OF USING THESAURUS TECHNOLOGY IN TEACHING ENGLISH” (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the integration of thesaurus technology in English language instruction for freshmen in higher education. By examining current literature and empirical studies, it highlights the benefits of digital thesauri in enhancing vocabulary acquisition, promoting learner autonomy, and improving language proficiency. The discussion underscores the role of thesaurus tools in facilitating nuanced understanding of synonyms and antonyms, thereby enriching students' lexical repertoire and communicative competence.